Corporate Reputation and Social Performance: The Importance of Fit - Brammer, Stephen J.; Pavelin, Stephen (Journal of Management Studies, 2006)
abstract Utilizing data on a sample of large firms, we estimate a model of corporate reputation. We find reputation, derived from the assessments of managers and market analysts, to be determined by a firm's social performance, financial performance, market risk, the extent of long‐term institutional ownership, and the nature of its business activities. Furthermore, the reputational effect of social performance is found to vary both across sectors, and within sectors across the various types of social performance. Specifically, our results demonstrate the need to achieve a ‘fit’ among the types of corporate social performance undertaken and the firm's stakeholder environment. For example, a strong record of environmental performance may enhance or damage reputation depending on whether the firm's activities ‘fit’ with environmental concerns in the eyes of stakeholders.